Experiments in the Heuristics of Human Information Processing - Swieringa, Robert; Gibbins, Michael; Larsson, Lars; Sweeney, Janet Lawson (Journal of Accounting Research, 1976)
Robert Swieringa, Michael Gibbins, Lars Larsson, Janet Lawson Sweeney, Experiments in the Heuristics of Human Information Processing, Journal of Accounting Research, Vol. 14, Studies on Human Information Processing in Accounting (1976), pp. 159-187